The Influence of Price and Service Quality on Customer Satisfaction at T. Nogo Baru Motor Workshop in Surabaya - Wiwik Prihartanti; Ahmad Gamal (Madani: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to determine the effect of price and service quality on customer satisfaction at T Nogo Baru Motor Workshop in Surabaya. The study used a sample of 100 respondents obtained through a saturated sampling method. The data collection technique employed was a questionnaire distributed to respondents. A quantitative method with multiple linear regression analysis using SPSS version 23 was applied in this research. The results indicate that price and service quality partially have a significant effect on customer satisfaction at T Nogo Baru Motor Workshop in Surabaya. Meanwhile, price and service quality simultaneously have a significant effect on customer satisfaction at T Nogo Baru Motor Workshop in Surabaya. Based on the coefficient of determination test, the results show that price and service quality contribute 66.2% to customer satisfaction, while the remaining 33.8% is influenced by other variables not examined in this study.